Anion-cation co-doped modified lithium manganese iron phosphate positive electrode material and preparation method thereof
By using anion and cation co-doping and carbon layer coating technology in the positive electrode materials of lithium iron phosphate, the problems of low conductivity and insufficient tap density of lithium iron phosphate materials are solved, and the stability and electrochemical performance of the material are significantly improved. It realizes efficient lithium ion migration channels and low-cost production.
Patent Information
- Application Number
- CN202411212756.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
The existing lithium-ion battery cathode material lithium iron phosphate has problems such as low conductivity, insufficient tap density and high energy consumption per unit of production, and multi-element co-doping technology is difficult to effectively improve its electrochemical performance.
Modified lithium manganese phosphate positive electrode material with anion and cation co-doped anion and cation doping, and combined with carbon layer coating technology, the stability and conductivity of the material are improved and the conductivity of lithium ions are increased. migration channel.
It significantly improves the stability, capacity and conductivity of the material, improves the electrochemical performance, and is simple in preparation, easy to implement, and reduces production costs.
Smart Images

Figure CN119133440A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an anion-cation co-doped modified lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] In the era of energy crisis and rapid development of electronic devices, lithium-ion batteries have become a research hotspot as a high-energy-density, safe, and inexpensive energy storage device. 4 ) has a stable crystal structure, high specific capacity, stable discharge platform and long cycle life, and is one of the preferred positive electrode materials for lithium-ion power batteries. However, as a key material for power batteries, it has three defects: first, low conductivity, which makes it difficult to exert the specific capacity and rate performance of the material; second, low tap density, which greatly affects its energy density; third, high unit energy consumption and large exhaust gas emissions during the production process. LiMnPO 4 LiFePO 4 The isomer of LiFePO has a higher working voltage (4.1 V vs. Li / Li+), making it a promising candidate for use as a catalytic converter compared to LiFePO 4 However, due to the dissolution of Mn, LiMnPO 4 The electronic conductivity and cycle life are also poor (<10 -10 S cm -2 ). Appropriate element doping can often improve LiMnFePO to a certain extent. 4 Performance of cathode materials, multi-element co-doped LiMnFePO 4 It is expected to become an important way to effectively improve its electrochemical performance.
[0003] Patent CN116514088A uses ball milling to achieve fluorine doping. Although the particles are reduced, the shape is difficult to control. At the same time, the equipment required for the scale-up experiment is expensive, especially large-capacity grinders or grinders with special functions, which becomes an obstacle for small-scale or low-budget operations. Patent CN114373912B discloses the use of graphene to form a conductive network. Although the conductivity of the material is enhanced, the cost of graphene is relatively expensive. The use of scaled-up production will reduce the cost of benefits; and the use of sucrose, polypyrrole and graphene to coat carbon at the same time is difficult to control the thickness of the carbon layer in terms of technical means. The thickness of the carbon layer will affect the migration rate of lithium ions. Carbon nanotubes can reduce agglomeration to a certain extent after acid treatment, but due to the inherent properties of inorganic carbon sources, it is difficult to disperse evenly in a short time during sand milling. The local carbon layer of the synthesized material is unevenly coated, and the addition of the acid treatment step will increase the cost, and it also involves the treatment of waste acid. Patent CN115954460A prepared lithium iron manganese phosphate by electrospinning. The material has a flaky morphology and low compaction compared to the smooth spherical and large single crystal morphology of lithium iron manganese phosphate. Patent CN105470468A prepared fluorine-doped lithium iron manganese phosphate by hydrothermal method. The fluorine content of this patent is relatively high, and the electrical properties are improved only by single fluorine doping. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the present invention provides a modified lithium iron manganese phosphate positive electrode material co-doped with anions and cations and a preparation method thereof. The modified lithium iron manganese phosphate positive electrode material of the present invention is doped with fluorine ions at the oxygen position to inhibit the dissolution of manganese ions, thereby improving the stability of the olivine structure. At the same time, since the radius of the fluorine ions is smaller than that of the oxygen ions, the bond length is increased and the bond energy is reduced, so that the stability of the lithium iron manganese phosphate olivine structure is increased and the migration channels of lithium ions are increased, thereby improving the capacity and stability of the material; doping cations at the iron position can improve the electrical conductivity and compaction density of the material.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is: A modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations, comprising lithium manganese iron phosphate doped with anions and cations and a carbon layer, wherein the carbon layer is coated on the surface of the lithium manganese iron phosphate doped with anions and cations, and the chemical general formula of the lithium manganese iron phosphate doped with anions and cations is LiMn 0.6 Fe 0.4-x M x PO 4-y Y y , wherein 0.001≤x≤0.03, 0.01≤y≤0.5, M is a cation, and Y is a fluoride ion.
[0006] In another aspect, the present invention provides a method for preparing the anion-cation co-doped modified lithium manganese iron phosphate positive electrode material, comprising the following steps: (1) mixing a lithium source, a manganese source, an iron source, a cationic dopant, a phosphorus source, an anionic dopant and a carbon source, adding deionized water, and heating the mixture for reaction to obtain a precursor; (2) The precursor is calcined at high temperature under the protection of an inert gas atmosphere to obtain a carbon layer-coated, doped and modified lithium manganese iron phosphate positive electrode material.
[0007] Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate; The phosphorus source is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, and pyrophosphoric acid; The manganese source is one or more of manganese sulfate, manganese chloride and manganese carbonate; The iron source is one or more of ferrous sulfate, ferrous chloride, and ferrous oxalate; The anion dopant is one or more of lithium fluoride, polyvinylidene fluoride, and ammonium fluoride; The cationic dopant is one or more of ammonium molybdate, ammonium metavanadate, niobium pentoxide, and titanium dioxide.
[0008] Preferably, in step (1), the molar ratio of the lithium source, the manganese source, the iron source, the cationic dopant, the phosphorus source and the anionic dopant is 1.0-1.1:0.6:0.4-x:x:4-y:y.
[0009] Preferably, the carbon source is one or more of glucose, sucrose, polyethylene glycol, and citric acid.
[0010] More preferably, the carbon source is sucrose and polyethylene glycol in a mass ratio of 1-2:1.
[0011] More preferably, the polyethylene glycol is PEG2000.
[0012] Preferably, in step (1), the amount of the carbon source added is 5%-9% of the total mass of the lithium source, manganese source, iron source, cationic dopant, phosphorus source and anionic dopant; The amount of water added is 2-3 times the total mass of the lithium source, the manganese source, the iron source, the cationic dopant, the phosphorus source and the anionic dopant.
[0013] Preferably, in step (1), the reaction temperature is 140-180° C. and the reaction time is 16-24 h.
[0014] Preferably, step (1) further comprises, after the reaction is completed, filtering and washing the reactants and then vacuum drying them to obtain a precursor, and the number of washing times is not less than 2 times.
[0015] Preferably, in step (2), the inert gas is nitrogen or argon.
[0016] Preferably, in step (2), the high temperature calcination temperature is 500-800°C, the heating rate is 2-10°C / min, and the calcination time is 4-10h.
[0017] The present invention also provides the use of the modified lithium iron manganese phosphate positive electrode material in preparing a positive electrode of a lithium ion battery.
[0018] The anion-cation co-doped modified lithium iron manganese phosphate material prepared by the above method has significantly improved material stability and rate performance when used to prepare positive electrode materials for lithium-ion batteries.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. In the lithium iron manganese phosphate positive electrode material of the present invention, fluorine ions can inhibit the dissolution of manganese ions, thereby increasing the stability of the lithium iron manganese phosphate olivine structure and increasing the migration channel of lithium ions, thereby improving the capacity and stability of the material; metal ions can improve the conductivity and compaction density of the material. After performance testing, the material of the present invention has significantly improved stability and discharge capacity compared to electrode materials not doped with anions and cations, effectively improving the electrochemical performance of the lithium iron manganese phosphate positive electrode material.
[0020] 2. The present invention realizes carbon layer coating and anion and cation co-doping modification simultaneously through a one-step hydrothermal method, and the preparation method is simple and easy to implement; the conductivity of the material is improved by coating with inorganic carbon sources and organic carbon sources; the improvement of gram capacity and cycle performance is achieved by doping with a small amount of fluorine combined with metal ion doping, thereby effectively improving the comprehensive performance of lithium manganese iron phosphate positive electrode materials.
[0021] 3. The modified lithium manganese iron phosphate positive electrode material prepared by the present invention has an irregular spherical shape, a relatively smooth particle surface, a graded distribution of large and small particles, and a high compaction; by simultaneously doping anions and cations, the electrical properties, compaction and material stability of the material are significantly improved, and its 0.1C discharge capacity is as high as 159.17 mAh / g, and the compaction density is as high as 2.35 g / cm 3 , with excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 is a scanning electron microscope image of the lithium manganese iron phosphate material prepared in Example 2 of the present invention; Figure 2 This is a 0.1C charge and discharge curve of a button cell assembled with lithium manganese iron phosphate material prepared in Example 2 of the present invention; Figure 3 This is a 1C charge and discharge curve of a button-type battery assembled with lithium manganese iron phosphate material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0023] Embodiment 1: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, 0.042g of lithium fluoride, and 0.688g of ammonium metavanadate were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3953 V 0.0047 PO 3.987 F 0.013 .
[0024] Embodiment 2: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, 0.055g of lithium fluoride, and 0.688g of ammonium metavanadate were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3953 V 0.0047 PO 3.966 F 0.034 .
[0025] Embodiment 3: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, 0.068g of lithium fluoride, and 0.688g of ammonium metavanadate were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3953 V 0.0047 PO 3.979 F 0.021 .
[0026] Embodiment 4: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, 0.055g of lithium fluoride, and 1.514g of niobium pentoxide were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3957 Nb 0.0043 PO 3.966 F 0.034 .
[0027] Embodiment 5: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, and 0.854g of titanium dioxide were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.39 2 Ti 0.008 PO 3.966 F 0.034 .
[0028] Comparative Example 1: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, and 0.483g of ammonium metavanadate were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3967 V 0.0033 PO 4 .
[0029] Comparative Example 2: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, and 0.688g of ammonium metavanadate were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3953 V 0.0047 PO 4 .
[0030] Comparative Example 3: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 7.70g of PEG2000, and 0.908g of ammonium metavanadate were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.3938 V 0.0062 PO 4 .
[0031] Comparative Example 4: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, and 7.70g of PEG2000 were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.4 PO 4 .
[0032] Comparative Example 5: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 0.055g of lithium fluoride, and 7.70g of PEG2000 were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain a lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.4 PO 3.966 F 0.034 .
[0033] Comparative Example 6: 76.74g of ferrous sulfate, 57.72g of manganese sulfate, 19.31g of lithium carbonate, 74.24g of phosphoric acid, 11.40g of sucrose, 0.504g of magnesium oxide, and 7.70g of PEG2000 were placed in a reactor in sequence, and 500g of deionized water was added to the reactor, and the reaction was carried out at 180°C for 24h. After the reaction, the material was centrifuged and washed three times, and then dried to obtain lithium iron manganese phosphate precursor powder; it was placed in a tubular furnace under a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain a carbon layer-coated lithium iron manganese phosphate material LiMn 0.6 Fe 0.39 Mg 0.01 PO 4 .
[0034] The anion- and cation-modified lithium manganese iron phosphate positive electrode materials prepared in the above examples and comparative examples were assembled into button batteries and electrochemical performance tests were performed. The results are shown in Tables 1 and Figure 2-3 .
[0035] Table 1 Performance test results of batteries assembled in the embodiments and comparative examples
[0036] As can be seen from Table 1 and Comparative Examples 1-5, the doping of a single vanadium can effectively reduce polarization and improve the compaction and electrical properties of the material; the doping of a single fluorine ion increases the electrical properties of the material, and the platform medium pressure is steadily improved. Compared with Comparative Examples 1-6, Examples 1-5 and 1-6 show that metal ion doping can improve the compaction density of the material, anion dopants can significantly improve the gram capacity and rate performance of the material, and anion and cation co-doping simultaneously improves the electrical properties, compaction and stability of the material. It can be seen that the present invention significantly improves the comprehensive performance of lithium manganese iron phosphate materials through anion and cation co-doping.
[0037] Figure 1 is the SEM picture of Example 2 of the present invention, Figure 1It can be seen that the lithium manganese iron phosphate prepared by the method of the present invention has an irregular spherical shape, a relatively smooth particle surface, a graded distribution of large and small particles, and a high compaction. It can be seen that the present invention improves the compaction density and capacity of the material through the synergistic effect of anion and cation dopants, and effectively improves the electrochemical performance of the material.
[0038] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations, characterized in that: It includes anion- and cation-doped lithium manganese iron phosphate and a carbon layer, wherein the carbon layer is coated on the surface of the anion- and cation-doped lithium manganese iron phosphate, and the chemical formula of the anion- and cation-co-doped lithium manganese iron phosphate positive electrode material is LiMn 0.6 Fe 0.4-x M x PO 4-y Y y , wherein 0.001≤x≤0.03, 0.01≤y≤0.5, M is a cation, and Y is a fluoride ion.
2. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 1, characterized in that: The steps include: (1) mixing a lithium source, a manganese source, an iron source, a cationic dopant, a phosphorus source, an anionic dopant and a carbon source, adding deionized water, and heating the mixture for reaction to obtain a precursor; (2) The precursor is calcined at high temperature under the protection of an inert gas atmosphere to obtain a carbon layer-coated, doped and modified lithium manganese iron phosphate positive electrode material.
3. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: In step (1), the lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate; the phosphorus source is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, and pyrophosphoric acid; the manganese source is one or more of manganese sulfate, manganese chloride, and manganese carbonate; the iron source is one or more of ferrous sulfate, ferrous chloride, and ferrous oxalate; the anion dopant is one or more of lithium fluoride, polyvinylidene fluoride, and ammonium fluoride; and the cation dopant is one or more of ammonium molybdate, ammonium metavanadate, niobium pentoxide, and titanium dioxide.
4. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: In step (1), the molar ratio of the lithium source, the manganese source, the iron source, the cationic dopant, the phosphorus source and the anionic dopant is 1.0-1.1:0.6:0.4-x:x:4-y:y.
5. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: In step (1), the carbon source is one or more of glucose, sucrose, polyethylene glycol, and citric acid.
6. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: In step (1), the amount of the carbon source added is 5%-9% of the total mass of the lithium source, manganese source, iron source, cationic dopant, phosphorus source and anionic dopant; The amount of water added is 2-3 times the total mass of the lithium source, the manganese source, the iron source, the cationic dopant, the phosphorus source and the anionic dopant.
7. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: In step (1), the reaction temperature is 140-180° C. and the reaction time is 16-24 h.
8. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: Step (1) also includes, after the reaction is completed, filtering, washing, and vacuum drying the reactants to obtain a precursor.
9. The method for preparing a modified lithium manganese iron phosphate positive electrode material co-doped with anions and cations according to claim 2, characterized in that: In step (2), the high temperature calcination temperature is 500-800°C, the heating rate is 2-10°C / min, and the calcination time is 4-10h.
10. Use of the anion-cation co-doped modified lithium iron manganese phosphate positive electrode material according to claim 1 in preparing a positive electrode for a lithium ion battery.
Citation Information
Cited By
Method for improving compaction density of lithium ferric manganese phosphate positive electrode material
CN120573672A
Process for preparing lithium ferric manganese phosphate by low-cost two-firing process
CN121158755A
Cerium-lanthanum co-doped coated modified lithium manganese iron phosphate, preparation method and positive electrode
CN121202103A
Preparation process of high-cycle vanadium manganese iron lithium phosphate electrode material
CN121553918A
Preparation process of high-cycle vanadium phosphate manganese lithium iron electrode material
CN121553918B
